2017
DOI: 10.1194/jlr.m071274
|View full text |Cite
|
Sign up to set email alerts
|

AAV9-NPC1 significantly ameliorates Purkinje cell death and behavioral abnormalities in mouse NPC disease

Abstract: Niemann-Pick type C (NPC) disease is a fatal inherited neurodegenerative disorder caused by loss-of-function mutations in the or gene. There is no effective way to treat NPC disease. In this study, we used adeno-associated virus (AAV) serotype 9 (AAV9) to deliver a functional gene systemically into mice at postnatal day 4. One single AAV9-NPC1 injection resulted in robust NPC1 expression in various tissues, including brain, heart, and lung. Strikingly, AAV9-mediated NPC1 delivery significantly promoted Purkinj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 41 publications
1
33
0
1
Order By: Relevance
“…Other attractive approaches, evaluated in preclinical models of disease, include the systemic delivery of adeno-associated virus vectors to NPC1 -/- mice to increase the expression of a therapeutic NPC1 transgene, which has resulted in an improved clinical appearance, delayed weight loss, significantly increased life span, reduced cholesterol storage, and decreased cerebellar Purkinje cell degeneration compared with untreated NPC1 -/- mice 180 , 181 .…”
Section: Treatmentsmentioning
confidence: 99%
“…Other attractive approaches, evaluated in preclinical models of disease, include the systemic delivery of adeno-associated virus vectors to NPC1 -/- mice to increase the expression of a therapeutic NPC1 transgene, which has resulted in an improved clinical appearance, delayed weight loss, significantly increased life span, reduced cholesterol storage, and decreased cerebellar Purkinje cell degeneration compared with untreated NPC1 -/- mice 180 , 181 .…”
Section: Treatmentsmentioning
confidence: 99%
“…Gene therapy using adeno-associated viral vectors (AAV) administered to the central nervous system as potential treatments for neurodegenerative lysosomal storage disorders has transitioned from pre-clinical studies to clinical trials (NCT01801709, NCT00151216, NCT01414985, NCT02725580, NCT01474343 and ISRCTN19853672). For NP-C, there have already been two published pre-clinical studies using AAV9 to partially ameliorate symptoms in the Npc1 − / − , BALB/cNctr- Npc1 m1N /J mouse model ( 19 , 20 ). Both utilize the ability of AAV9 to cross the blood–brain barrier and administer the vector via systemic intravenous or intracardial injection.…”
Section: Introductionmentioning
confidence: 99%
“…--SRT (Platt et al, 1997) (Sango et al, 1995) + + AAV (Sargeant et al, 2011;Cachon-Gonzalez et al, 2014), BMT (Norflus et al, 1998;Wada et al, 2000), CM (Pelled et al, 2003), Diet (Denny et al, 2010), HSP (Kirkegaard et al, 2016), MIP-1 (Wu and Proia, 2004), SRT (Jeyakumar et al, 1999) HexB ( Npc1 (−/−) (Morris et al, 1977) + -AAV (Chandler et al, 2017b;Xie et al, 2017;Hughes et al, 2018), AI (Alvarez et al, 2008), AO (Fu et al, 2013), CM (Erickson et al, 2000;Repa et al, 2007;Abi-Mosleh et al, 2009;Liu et al, 2010;Taylor et al, 2012;Hovakimyan et al, 2013;Nusca et al, 2014;Tanaka et al, 2014;Soga et al, 2015;Demais et al, 2016), Diet (Jelinek et al, 2015;Soga et al, 2015), HSP (Chung et al, 2016;Kirkegaard et al, 2016), NS (Griffin et al, 2004;Liao et al, 2009), Transplant (Veyron et al, 1996) Npc1 (Otterbach and Stoffel, 1995) + +…”
Section: Metachromatic Leukodystrophymentioning
confidence: 99%
“…The I1061T mutant, which harbors the most common human NPC1 mutation, was generated to specifically study the effects of proteostatic modulation on disease progression. Various preclinical trials including GT, ERT, and transplant in these models have shown different but promising levels of success in prolonging mutant lifespan, reducing Purkinje cell atrophy and the storage phenotype (Veyron et al, 1996;Soga et al, 2015;Chandler et al, 2017b;Xie et al, 2017;Hughes et al, 2018).…”
Section: Metachromatic Leukodystrophy (Mld Omim #250100)mentioning
confidence: 99%